The Psychological Impact of Early Marriage on Family Harmonization - Setiyawanti, Retni; Putra, Anggar (International Journal on Advanced Science, Education, and Religion, 2025)
Early marriage remains an important issue in Indonesia, as noted in the 2024 Report on People's Welfare Indicators by the Central Statistics Agency (BPS). The majority of women in Indonesia marry for the first time between the ages of 19 and 24, with a proportion reaching 49.58%, an increase of 0.57% compared to 2023. The research method used is qualitative with a phenomenological approach. The data sources are library research, primary data, and secondary data from readings (laws and regulations, legal books, legal journals, and literature related to the subject of study in the field of law). The collected data is then analyzed using descriptive analysis techniques and conclusions are drawn. Early marriage, although justifiable from an Islamic legal perspective under certain conditions, has the potential to cause significant negative impacts from a psychological aspect, such as anxiety, stress, and unpreparedness in fulfilling the roles of husband or wife, which may disrupt marital harmony. According to Indonesian legal provisions, the minimum age for marriage is 19 years, aimed at ensuring the physical and mental readiness of the parties involved. Therefore, early marriage can be justified in certain situations, such as to avoid adultery or in the case of pregnancy outside of marriage, but the decision to marry should be based on careful consideration of the physical and psychological readiness of the couple. The principle of maslahah mursalah emphasizes that early marriage should only be conducted in urgent circumstances and after considering the welfare and harmony of the family.